Dynamic machine layout for press tool operations using real coded genetic algorithm. (2016) - Chandratre, Kailas V.; Pawar, Padmakar J.; Nandurkar, Keshav N.
In today's economy, manufacturing plants must be able to operate efficiently and respond quickly to changes in the product mix and demand. Layout design has a significant impact on manufacturing efficiency. A static plant layout if possible to be converted to dynamic layout may improve the efficiency of the plant significantly. Dynamic layout is a layout which can be rearranged with respect to time as per variation in product design, quantity and change in product mix. Dynamic layout problem is a quadratic assignment problem and is of non-deterministic polynomial-time hard problem. In this work, an attempt is made to solve this problem using real coded genetic algorithm (GA), which overcomes some of the limitations of traditional GA. This algorithm has been applied to the dynamic layout benchmark problems to prove its effectiveness. In addition, a real life example is considered to validate the presented approach.